Experience with an evolving overlay network testbed. - Andersen, David G. (Computer communication review.)
The MIT RON testbed consists of 36 Internet-connected nodes at 31 different sities. It has been in operation for two years. This paper presents an overview of the testbed, summarizes some of the research for which it has proved useful, and presents the lessons we learned during its development. The testbed has been useful both for our own research and for that of external researchers becuase of its heterogeneous, diverse network connections; its homogenous hardware and software platform; its incremental, bottom-up development; and its easy configuration and management tools.